Analysis of genotoxic and cytotoxic effects of oral mucosa in smokers and non-smokers after exposed to digital intraoral radiography - Dwi P. Wulansari; Aryadi Arsyad; Irene E. Rieuwpassa; Nurlindah Hamrun; Rafikah Hasyim (Journal of Dentomaxillofacial Science, 2019)
Objectives : To analyze genotoxic and sitotoxic indicators of buccal epithelial cells by measuring the number of cells contain micronucleus, pycnosis, karyorrhexis, karyolysis and to determine the change in oxidative stress of  oral mucosa cells using salivary MDA levels between smokers and nonsmokers before and after exposure to intraoral radiographs during endodontic treatment.Material and Methods : This research was an analytic observation research with cross-sectional design. The sample was divided into smokers (n = 5) and non-smokers group (n = 5). The buccal epithelial cells was taken with cytobrush and unstimulated saliva in each group were taken by the draining method shortly before intraoral radiography, 10±2 days after first  day exposure, 10±2 days after second day exposure. The cells were stained using Papanicolau (PAP) kit and observed by pathologist. Genotoxic and cytotoxic indicator measured by counted the number of cells contain mironucleus, pyknosis, karyorrhexis and karyolysis under light microscope with 400X magnification according to the Tolbert criteria in 1000 cells. While oxidative stress of cell measured by salivary MDA with Thiobarbitoric Acid (TBA) assay.Result : The number of micronucleus, pyknosis, karyorrhexis, karyolysis in buccal epithelial cells and salivary MDA levels in smokers was higher than non-smokers (p<0,05). There were no significant differences in genotoxic and cytotoxic indicators and salivary MDA levels before and after the last exposure in smokers and non-smokers (p>0,05).Conclusion : The results of this study indicate that the use of intraoral radiographs is within safe limits despite repeated exposure after several days.